The ethanol Production Activity of Indigenous Thermotolerant Yeast Pichia kudriavzevii 1P4 - DAROJATUL ULYA; RIKA INDRI ASTUTI; ANJA MERYANDINI (Indonesian Society for microbiology, 2020)
Pichia kudriavzevii 1P4 is a thermotolerant-ethanologenic yeast potential for application in ethanol industry. In this study we evaluated the stress tolerance phenotype of P. kudriavzevii 1P4 in dealing with fermentation related-stresses, including high temperature stress, high sugar content, ethanol content and the fermentation capacity of the particular isolate. Based on spot assay, 1P4 showed stress tolerance phenotype against high sugar concentration for up to 30% sugar content and 10% ethanol stress. In addition, 1P4 was capable to show temperature-stress tolerance phenotype for up to 42oC, suggesting that 1P4 belong to thermotolerant yeast isolate. Fermentative activity was measured by using glucose consumption and ethanol production assay. We evaluated the fermentative and growth rate of 1P4 at various temperature condition which were 27oC, 37oC and 42oC using YPD media (at initial glucose of 2%, 10% and 20%). Interestingly, 1P4 consumed the highest glucose in 20% of concentration at 37oC (15.29%), simultaneously with the highest concentration of ethanol (32.05 g/L ethanol and 0.67 g/L/h ethanol productivity). Cell growth analysis showed that growth of 1P4 isolate increased with higher initial glucose condition yet decreased as temperature during fermentation was raised. The growth rate of 1P4 was found high in 20% initial glucose at 37oC than 2% and 10% at same temperature. In addition, 1P4 exhibited short lag phase at high-temperature fermentation. Our data indicate that 1P4 can potentially be applied as fermentation agent especially in high-temperature ethanol fermentation. Key words: bioethanol production, fermentation related-stress, thermotolerant yeast